Ordinance No. 201., COFFEYVILLE WEEKLY JOURNAL, Feb. 7, 1890, at 2. (Coffeyville, KS). - (:unkn) unknown (General Publisher, 1890)
Any person, other than a peace officer, of the city, or a peace officer of the State of Kansas, or some County, City or Township in the State, who shall be found within the corporate limits of the City of Coffeyville, at any time, having upon his or her person, concealed or otherwise, without first having obtained permission from the Mayor, a revolver, pistol, dirk-knife, bowie-knife, sling shot, metallic knuckles, or any other dangerous or deadly weapon, shall be deemed guilty of a misdemeanor, and upon conviction, shall be sentenced to pay a fine of not less than one nor more than fifty dollars, or to be imprisoned in the City Jail not less than one day nor more than ten days, or to both fine and imprisonment, at the discretion of the Police Judge.
--
Keywords: CARRY - CONCEALED